Sources of perceived self-efficacy as predictors of physical activity in older adults - Warner, Lisa Marie; Schüz, Benjamin; Knittle, Keegan; Ziegelmann, Jochen P.; Wurm, Susanne (Applied psychology: health and well-being, 2011)
According to Bandura's self-efficacy theory, there are four sources of self-efficacy: past experience, vicarious experience, verbal persuasion, and perception of physical states. The aims of the study were twofold: To review previous research on the sources of self-efficacy and to examine the sources in predicting self-efficacy for exercise in older adults. A sample of 309 older adults was assessed at two time points for exercise, exercise-specific self-efficacy, and four sources of self-efficacy. Past experiences, vicarious experiences, and subjective health had significant direct effects on self-efficacy and indirect effects on exercise via self-efficacy. Persuasive arguments did not predict self-efficacy. This suggests that future research should target past experience and vicarious experience as sources of self-efficacy. © 2011 The Authors. Applied Psychology: Health and Well-Being © 2011 The International Association of Applied Psychology.
Keywords: Exercise; Multimorbidity; Objective health; Sources of self-efficacy; Subjective health